Electrochemical Degradation of Reactive Black 5 Using Two-Different Reactor Configuration - Cifuentes-Molina, G; Droguett-Villalobos, T (Nature Research, 2020)
Novel Sb-doped SnO2 ceramic electrodes sintered at different temperatures, are applied to the degradation of Reactive Black 5 in both divided and undivided electrochemical reactors. In the undivided reactor the discoloration of the solution took place via the oxidation of RB5 dye, without the corresponding reduction in the chemical oxygen demand for the ceramic electrodes. However, in the divided one, it was possible to achieve the discoloration of the solution while at the same time decreasing the chemical oxygen demand through the ·OH-mediated oxidation, although the chemical oxygen demand degradation took place at a slower rate. © 2020, The Author(s).